Impact of vernalization on flowering, fruiting, and yield of strawberry (Fragaria × ananassa) cultivars under tropical highland conditions - ESCOMEN, EDGEL O.; JAMBARO, GERLIE S. (Asian Journal of Agriculture, 2026)
Abstract. Escomen EO, Jambaro GS. 2026. Impact of vernalization on flowering, fruiting, and yield of strawberry (Fragaria × ananassa) cultivars under tropical highland conditions. Asian J Agric 10 (1): g100116. https://doi.org/10.13057/asianjagric/g100116. Vernalization is a key physiological process influencing flowering, fruiting, and yield in strawberry, yet its effectiveness varies among cultivars, particularly under tropical highland conditions where natural chilling is limited. This study examines the performances of vernalization in terms of phenology, productivity, and fruit characteristics of five strawberry cultivars, namely Albion, Snow White, Summer Princess, Sweet Charlie, and Sweet Honeoye. The experiment was conducted in the tropical highland environment in Marawi City, Philippines, to improve strawberry production in tropical and subtropical areas. A 2x5 split-plot in Randomized Complete Block Design (RCBD) with vernalization (3°C for 10 h before planting) as the main plot and cultivar as the subplot. Vernalization significantly accelerated flowering, increased flower and fruit numbers, and enhanced total yield across cultivars (p
Keywords: Flowering induction, fruit yield, strawberry cultivars, temperature manipulation, vernalization